Tasa de depredación de Coralliophila abbreviata (Neogastropoda: Coralliophilidae) sobre algunas especies coralinas del Parque Nacional Morrocoy, Venezuela - del Mónaco, C. (Universidad de Costa Rica, 2008)
Coralliophila abbreviata is a tropical gastropod of the Caribbean Sea. This gastropod is an important corallivore. The objective of this work was to estimate the predation rate of C. abbreviata on some coral species in the coral reefs of Morrocoy National Park, Venezuela. The localities were Cayo Sombrero and Cayo Peraza. We evaluated the rate on five coral species: Montastraea annularis, Colpophyllia natans, Diploria strigosa, Diploria labyrinthiformis and Agaricia agaricites. We used three experimentals treatments. In treatment 1 we marked colonies with buoys that had been predated by C. abbreviata. In treatments II and III we used exclusion cages. Treatment II included the colony with its predators and treatment III was the control (only the colony). The injuries of the colonies were measured every 4 days for at least a month. The predation rate in treatment I varied depending on the coral species. The highest rate was on C. natans (3.70 cm2/Ind/day), while D. strigosa, D. labyrinthiformis and M. annularis did not register any predation rate (0 cm2/Ind/day). In treatment II we only detected predation activity in 1 colony of M. annularis with 0.15 cm2/Ind/day. The main effect generated by C. abbreviata on the Morrocoy National Park's coral reefs could be a decrease in the colonies reproduction and growth rate due to energetic use in tissue regeneration of injuries.